Developing a Learning Module About Integers for 7th Grade Students through Writing-to-Learn - Lie, Margaretha Weryana; TLS, Desyarti Safarini (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2021)
Previous research shows that seventh-grade students lack a sense of flexibility about numbers, lack comprehension of the effect of the operation on numbers, and lack estimation skills. On the other hand, writing to learn is one of the learning activities where the students actively write to express themselves in learning specific material/topic. This project aims to develop a learning module for students about the integers by utilizing the basic number sense framework: the six strands of number sense (Mcintosh et al., 1997) and combining it using writing to learn mathematics (Burns, 1995). The module developed using the steps proposed by Purwanto (2007) and then validated by the experts and tested to the subjects’ trial. The module was then validated by three experts who are lecturers at Sampoerna University. After validation, the module was then tested on four seventh-grade students, where the data gathered by both observation and group interview. As a result, all participants agree that the learning module is easier than what they taught at school and would recommend the module to their friends.